การกำกับดูแลและแทรกแซงเว็บบอร์ดทางการเมืองหลังเหตุการณ์รัฐประหาร 19 กันยายน 2549 - บัณฑิต จำรูญวงศ์สกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This thesis aims at studying state regulation and interference of political webboards in Thailand and the responses it evoked by the Internet industry and civil society during the period subsequent to the 19 September 2006 coup d’etat. The research is qualitative in nature. Data collection was done through content analysis and in-depth interviews. The study finds that after the 19 September 2006 coup d’etat, the control of political webboards was administered primarily through these means: legal enforcement and blogging of websites. Two laws were issued during this time -- Decree 5 of the Council for Democratic Reform (CDR) which staged the coup and the Computer Crime Act 2007. The Ministry of Information and Communication Technology (MICT) which has been in charge of website blocking since 2002 is the main mechanism in carrying out the regulatory task. The study finds that the MICT administers the control of political webboards by warning to webmasters to delete or watch out for problematic content while notifying web hosting services, Internet Service Providers (ISPs) as well as CAT Telecom Public Co., Ltd. to block websites of political weboards. In the case of CAT Telecom which is the main service provider of international Internet gateways in Thailand, the study finds blocking occurs at this level. The study also detects a certain pattern of control. For websites which are openly anti-coup, blocking was used disparagingly while those which are pro-coup would be spared of such measure and the government would be more lenient in their regulatory action. Meanwhile, under the post-coup context, the study finds that organization norm or policy, personal values, state power, and political circumstances are factors that varyingly influence the decision of webmasters in selecting and screening topics and content for their respective webboards. Lastly, based on interview with members from the local Internet industry and civil society, the study finds that these sectors prefer a more transparent policy regarding webboard and Internet regulation. They also recommend self-regulation by the industry and users or co-regulation rather than mere state regulation to ensure the needed transparency